The factors that influence the customer’s purchase intention towards harumanis produced by UiTM Perlis / Syazani Aniq Khairul Azmi - Khairul Azmi, Syazani Aniq (2021)
UiTM Perlis is among one of the public high learning institutions in Malaysia that have taken the opportunity in planting Harumanis because it provides agriculture courses and as well as having a large area of land for farming purposes. By selling Harumanis, it helps to generate revenue for the institution. To ensure that the sales meet the high market demands, UiTM Perlis has been focusing to produce Harumanis fruits that of high quality and quantity. In relation with that, the purpose of this study is to determine whether there is a relationship between promotion, price, attitude, and social influence with the customers’ purchase intention towards Harumanis produced by UiTM Perlis. This study involved 384 citizens of Perlis as respondents in Perlis. The instrument used in this study was a structured questionnaire through the snowball sampling technique. Frequency analysis, descriptive test, reliability analysis, Cronbach alpha, Pearson correlation analysis and regression analysis were used as an analytical technique. The data collected were analysed using the Statistical Package for Social Sciences (SPSS). The result of this study showed that there is a significant relationship between a dependent variable and the independent variables which are promotion, price, attitude, and social influence. Therefore, UiTM Perlis is expected to be more concerned in improving the promotion, price, attitude and social influence to improve its sales.